(untitled) (Research, Society and Development, 2020)
Introduction: The SARS-COV-2 virus causes the disease known as coronavirus or COVID-19 infection. Preventive measures for non-infection should be adopted, among them, the use of gloves by health professionals and the population in general is noted. Objective: to discuss the use of gloves by health professionals and the general population. Methodology: this is a descriptive-exploratory study, of the informative article type, based on scientific literature, the search was made between the 15th to the 23rd of May, in the Virtual Health Library (VHL) and Scielo libraries, as well as in documents from the World Health Organization and the Ministry of Health. Conducted without a time filter. Results: the use of gloves is an extremely important alternative for health professionals, but not indicated for the use of the general population. Emphasize that this use does not replace hand washing, reinforcing this hygienic importance and that when used they give themselves in an appropriate way. Conclusions: That these professionals do training and updates on hand washing and gloves use protocols. May the population be discouraged from using it, which can be done through the official pages and social media, as well as through direct professionals of Primary Care.